Mini-mu bacteriophage with plasmid replicons for in vivo cloning and lac gene fusing. - Groisman, E A (1986)
New mini-Mu transposons with plasmid replicons were constructed with additional features for in vivo DNA cloning and lac gene fusing in Escherichia coli. These mini-Mu replicons can be used to clone DNA by growing them with a complementing Mu bacteriophage and by using the resulting lysate to transduce Mu-lysogenic cells. These mini-Mu phage have selectable genes for resistance to kanamycin, chloramphenicol, and spectinomycin-streptomycin, and replicons from the high-copy-number plasmids pMB1 and P15A and the low-copy, broad-host-range plasmid pSa. The most efficient of these elements can be used to clone genes 100 times more frequently than with the previously described mini-Mu replicon Mu dII4042, such that complete gene banks can be made with as little as 1 microliter of a lysate containing 10(6) helper phage. The 39-kilobase-pair Mu headful DNA packaging mechanism limits the size of the clones formed. The smallest of the mini-Mu elements is only 7.9 kilobase pairs long, allowing the cloning of DNA fragments of up to 31.1 kilobase pairs, and the largest of them is 21.7 kilobase pairs, requiring that clones carry insertions of less than 17.3 kilobase pairs. Elements have been constructed to form both transcriptional and translational types of lac gene fusions to promoters present in the cloned fragment. Two of these elements also contain the origin-of-transfer sequence oriT from the plasmid RK2, so that clones obtained with these mini-Mu bacteriophage can be efficiently mobilized by conjugation.